Silence as Resistance before the Subject, or Could the Subaltern Remain Silent? - Roi Wagner (The February Journal, 2023)
This text considers several case studies of subaltern silence as micropolitical resistance. Around these examples the author threads a theoretical model (using ideas of such thinkers as Gayatri Spivak, Georges Bataille, Michel Foucault and Jean Baudrillard) to explain how performing silences could resist oppression without assuming an underlying well-articulated subjectivity. The paper deals with the force of silence, its conditions of possibility, and its position with respect to representation.